(untitled) (Journal of Bangladesh Academy of Sciences, 2012)
The strategic points of a pyralid insect, Synclita occidentalis (Pylralidae, Lepidoptera) on duckweed productivity, life cycle and its association with duckweed (host-plant) in pond ecosystem was studied. A total of 16 samples were used to study the infestation intensity and the impact of pest on duckweed production. The insect was found deeply associated with duckweed to complete its life cycle. The pyralid insect attains its pest status at larval stage and continues up-to the pupal stage. Larval and pupal case-making and feeding adaptations were noted as the characteristic nature of injury. The larvae build case with duckweed fronds and roots and use duckweed fronds that failed to multiply further. The crop of larva was the largest and widest part of the alimentary canal and varied exceedingly along with larval category. The experimental result indicated that pest impact in two different experimental miniponds was different in quantities but similar in mode of action. DOI: http://dx.doi.org/10.3329/jbas.v36i1.10920 Journal of Bangladesh Academy of Sciences, Vol. 36, No. 1, 53-59, 2012